Diversity of Ficus L. in Huay Nam Pam Forest Conservation Unit, San Pan Dan Wildlife Sanctuary, Pang Mapha District, Mae Hong Son Province - สุจริตใจ ณัชชา; ตันมิ่ง วัฒนา; อินตา อังคณา (KKU Science Journal, 2013)
Survey and study species diversity of Ficus spp. at Huay Nam Pam Forest Conservation Unit, San Pan Dan Wildlife Sanctuary, Pang Ma Pha District, Mae Hong Son Province were carried out between May 2012 and March 2013. Three survey lines were set up for data collecting with the total distance 10.35 kilometers. Twenty-seven species, 197 trees of Ficus species belonging to 6 subgenera were found. The largest subgenera is Urostigma, with 13 species, followed by Sycomorus with 7 species. Subgenera Ficus, Sycidium and Synoecia each with 2 species and Pharmacosycea with 1 species. Total number of Shannon and Weaver Index is 2.93. The first line had the most species composition and species diversity, followed by the third and second line respectively.